2020
DOI: 10.3390/en13010266
|View full text |Cite
|
Sign up to set email alerts
|

A Standard-Based Method to Simulate the Behavior of Thermal Solar Systems with a Stratified Storage Tank

Abstract: Thermal solar systems are interesting solutions to reduce CO 2 emissions and gradually promote the use of renewable sources. However, sizing such systems and analysing their behavior are still challenging issues, especially for the trade-off between useful solar energy maximization and stagnation risk minimization. The new EPB (Energy Performance of Buildings) standard EN 15316-4-3:2017 offers several methods to evaluate the performance of a forced circulation solar system. One of them is a dynamic hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This model, based on the operative temperature, is used to calculate product-specific values of setpoint variations, which are then used in heat loss calculations instead of tabulated values. Piana et al [23] have shown that EN 15316-4-3:2017 and EN 15316-5:2017 can successfully be applied in the design process of a solar thermal system. In their work, a non-invasive solar loop pump control model, allowing the quantification of the risk of stagnation resulting from increased solar field areas or decreased storage volume, is added to the standard framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model, based on the operative temperature, is used to calculate product-specific values of setpoint variations, which are then used in heat loss calculations instead of tabulated values. Piana et al [23] have shown that EN 15316-4-3:2017 and EN 15316-5:2017 can successfully be applied in the design process of a solar thermal system. In their work, a non-invasive solar loop pump control model, allowing the quantification of the risk of stagnation resulting from increased solar field areas or decreased storage volume, is added to the standard framework.…”
Section: Introductionmentioning
confidence: 99%
“…The reviewed studies usually deal with individual modules [22][23][24][25], but there were no studies found in which the overall calculation was performed with the goal of finding a cost-optimal solution. Hence, the main novelty of this study is in demonstrating the applicability and reliability of the overall complex and comprehensive calculation procedure, based on the new EPB standards for assessing the energy performance of a building.…”
Section: Introductionmentioning
confidence: 99%
“…However, although they offer great possibilities, their use requires specialised knowledge and experience. Hence, there is also a need for methods simpler but accurate enough to perform annual simulations with hourly time steps required by current standards and provide reasonable time resolution for thermal phenomena, occupation schedules, weather data and calculation accuracy [29][30][31], especially in terms of energy certification of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The main tool for decarbonization is the integration of renewable energy sources (RES), but this is a challenging task, mainly because of their variability in space and time. Solar energy, for instance, is an abundant source at most European latitudes, but it requires reliable tools to evaluate both the actual energy potential [18] and the correct sizing and operation of the system [19]. The mismatch between demand and supply is usually overcome through flexible-oriented solutions, like the installation of thermal energy storages (TES) [20]).…”
Section: Introductionmentioning
confidence: 99%